The dynamics of transactional communication in contract marriages within Cipanas community - Rizaldi Parani; Dinara Hizkiarin Verga; Herman Purba (Faculty of Communications Science, Dr. Soetomo University, 2024)
The phenomenon of contract marriages often found in Cipanas Village, Bogor is interesting because it is one of the ways chosen by people to quickly improve their welfare. It’s considered to have an impact on welfare improvement and poverty alleviation in rural communities. Therefore, this study aims to describe how the dynamics of contract marriages based on transactional communication can provide a sense of what is welfare for the people of Cipanas Village. This study applies a qualitative approach supported by the use of the phenomenological method. Data collection was carried out using semi-structured interviews and observations carried out in the field. Data validity is carried out through internal validity and as a measuring tool by checking the consistency of answers given through the same question to ther informants. The results of this study indicate that transactional communication becomes a tool in the verbal negotiation process until an agreement is formed between the parties involved in the practice of contract marriages. This agreement on exchange values that has been approved is considered a safety valve in the economic dimension, especially in creating improvements in people's living standards. The society views the practice of contract marriages as legal and not in violation of religious regulations. The contribution of this research is expected to be a reference for the government and further researchers who will be conducting further studies related to the phenomenon of contract marriages.